Hematopoietic Deficiency of miR-223 Attenuates Thrombosis in Response to Photochemical Injury in Mice - Hui Wang (Nature Portfolio, 2017)
Abstract Some studies have shown that levels of MicroRNA (miR)-223 derived from platelets in the plasma are reduced following inhibition of platelet function, while others have shown a correlation between low plasma miR-223 and high on-treatment platelet reactivity. The present study seeks to investigate the role of miR-223 in arterial thrombosis. A model of photochemical-induced carotid thrombosis was applied to miR-223 deficient mice and littermate (WT) controls. Mice deficient in miR-223 exhibited significantly prolonged times to occlusive thrombosis compared to WT mice indicating a protective effect of miR-223 deficiency. Bone marrow transplantation experiments confirmed that the hematopoietic pool of miR-223 was responsible for differences in thrombosis times. Transfusion of either WT platelets or extracellular vesicles derived from WT platelets were both sufficient to shorten thrombosis times in miR-223 deficient recipients. The effect of platelet transfusions on IGF-1R was explored. These experiments revealed that vascular IGF-1R was down-regulated by platelet miR-223. Furthermore, inhibition of IGF-1R abolished the protection conferred by miR-223 deficiency on thrombosis. In conclusion, platelet miR-223 is a regulator of arterial thrombosis following endothelial injury through effects on vascular wall IGF-1R. This study indicates that platelet miR-223 is a potential therapeutic target for prevention of arterial thrombosis.